Core self-evaluations associated with workaholism: the mediating role of perceived job demands. Issue 1 (17th August 2020) - An, Ying; Sun, Xiaomin; Wang, Kai; Shi, Huijie; Liu, Zhenzhen; Zhu, Yiming; Luo, Fang
Abstract : Purpose: Why do some employees choose to prolong their working hours excessively? The current study tested how core self-evaluations (CSEs) might lead to workaholism and how perceived job demands might mediate this relationship. Design/methodology/approach: Insights from the extant literature underpin the hypotheses on how CSEs would affect the development of workaholism through perceived job demands. A sample of 421 working people in China completed the online surveys, and the mediation model was tested using Mplus 7.0 (Muthén and Muthén, 1998–2012). Findings: This study found that different components of CSEs influence workaholism in different ways. Specifically, generalized self-efficacy positively predicts workaholism, whereas emotional stability negatively predicts workaholism. Moreover, most aspects of CSEs (generalized self-efficacy, emotional stability and locus of control) influence workaholism via perceived job demands, specifically via perceived workload but not via perceived job insecurity. Originality/value: The current study is the first to explore how individuals' fundamental evaluations of themselves (i.e. CSEs) relate to workaholism. The results are helpful for the prevention and intervention of workaholism in organizations.